Right ventricular energy metabolism in a porcine model of acute right ventricular pressure overload after weaning from cardiopulmonary bypass. Issue 22 (16th November 2022) - Kajimoto, Masaki; Nuri, Muhammad; Sleasman, Justin R.; Charette, Kevin A.; Kajimoto, Hidemi; Portman, Michael A.
Abstract: Acute right ventricular pressure overload (RVPO) occurs following congenital heart surgery and often results in low cardiac output syndrome. We tested the hypothesis that the RV exhibits limited ability to modify substrate utilization in response to increasing energy requirements during acute RVPO after cardiopulmonary bypass (CPB). We assessed the RV fractional contributions (Fc) of substrates to the citric acid cycle in juvenile pigs exposed to acute RVPO by pulmonary artery banding (PAB) and CPB. Sixteen Yorkshire male pigs (median 38 days old, 12.2 kg of body weight) were randomized to SHAM (Ctrl, n = 5), 2‐h CPB (CPB, n = 5) or CPB with PAB (PAB‐CPB, n = 6). Carbon‐13 ( 13 C)‐labeled lactate, medium‐chain, and mixed long‐chain fatty acids (MCFA and LCFAs) were infused as metabolic tracers for energy substrates. After weaning from CPB, RV systolic pressure (RVSP) doubled baseline in PAB‐CPB while piglets in CPB group maintained normal RVSP. Fc‐LCFAs decreased significantly in order PAB‐CPB > CPB > Ctrl groups by 13 C‐NMR. Fc‐lactate and Fc‐MCFA were similar among the three groups. Intragroup analysis for PAB‐CPB showed that the limited Fc‐LCFAs appeared prominently in piglets exposed to high RVSP‐to‐left ventricular systolic pressure ratio and high RV rate‐pressure product, an indicator of myocardial oxygen demand. Acute RVPO after CPB strongly inhibits LCFA oxidation without compensation by lactate oxidation, resulting in energy deficiency as determined by lower (phosphocreatine)/(adenosine triphosphate) in PAB‐CPB. Adequate energy supply but also metabolic interventions may be required to circumvent these RV energy metabolic abnormalities during RVPO after CPB. Abstract : Acute right ventricular pressure overload (RVPO) after cardiac surgery using cardiopulmonary bypass (CPB) is associated with inceased risk of RV failure. We found that (1) acute RVPO after CPB strongly inhibited FA, specifically long‐chain fatty acid (LCFA), oxidation in RV, and the FA metabolic abnormality correlated to RV‐to‐LV systolic pressure ratio inversely, and (2) lactate oxidation did not accelerate in response to the decreases in LCFA oxidation. These metabolic abnormalities can result in energy deficiency in RV under RVPO after CPB.